O Nordeste e o Mercado Nacional de Fragrâncias: notas para um mapa da produção/consumo de perfumes no Brasil - Maria Salete de Souza Nery (Ciências Sociais Unisinos)
From the symbolic embracing of the Boticário Group’s Distribution Center by the São Gonçalo community members (State of Bahia), at the interstate highway BR-101, this study seeks to understand fragrance market in Brazil and, specifically, the role the Northeast Region plays in it. Lastly, the study sought to understand the recent fluctuations shown in the national map of production and consumption of perfume, specifically between 2010 and 2016. It is assumed that fragrances relate to the symbolic realm and, therefore, are a cultural product full of meanings and traversed by capitalist interests.